Optimal tuning of parameters and structure of artificial neuron networks - Толстикова, Е. В. (Problems of Informatization and Control, 2012)
The task of optimal tuning of artificial neuron network with arbitrary structure parameters is considered. It is shown that for the wide class of artificial neuron networks it is possible to apply the modified gradient methods of search of optimal parameters for work of network in the conditions of measuring errors presence and external noises